Penyesuaian Rencana Pembelajaran dan Penerapan Aturan Kelas Efektif Dalam Pengelolaan Kelas Daring - Ekayani, Masithoh (Prosiding University Research Colloquium, 2021)
Education is necessary for the era's development. Knowledge and insight can get through education. School is one way to get a good education. A good school creates conducive learning conditions for students. Conducive learning constructs through effective teachers as well. One indicator of an effective teacher is a teacher who has good classroom management skills. Classroom management is one of the challenges for teachers, especially in the current state of the COVID-19 virus pandemic. Learning activities turned into Distance Learning or online activities that were face-to-face learning. Strategies that teachers could be done on online classes management are changing lesson plans and make online classes procedures. The creativity of teachers to use models, methods, learning media as well as give tasks and exercises in online classes is very important. The strict application of online classroom rules encourages students to focus and participating in online learning. Implementation of online learning following the planning and enforcement of procedures can create effective online learning so that learning purposes could be achieved.